Telecontrolling Microgreen Indoor Nursery Strawberry - Farida Arinie Soelistianto; Sandro Tri Alfian; Martono Dwi Atmadja (Jurnal Jaringan Telekomunikasi, 2023)
Strawberry is a horticultural commodity that produces a high economy, but in 2014 strawberry production decreased by 34.83%. The reason for the decrease in production is the unstable temperature and humidity conditions due to global warming. Another factor that causes strawberries to fail is due to the slowness of farmers in knowing changes in temperature and humidity in strawberry. The method used in this study was to compare the results of special treatment on microgreen strawberry nurseries indoor using natural vegetative methods and outdoor. System telecontrolling strawberry nursery real time with temperature and humidity parameters using a DHT22 sensor, soil moisture using a soil moisture sensor, soil pH using a soil pH sensor, time using RTC and light intensity using a light intensity sensor BH1750. The results of strawberry nurseries with telecontrolling an indoor plant height of 9 cm and a plant width of 12 cm, results of strawberry nurseries without telecontrolling treatment outdoor with a plant height of 7.5 cm and a plant width of 7 cm.